Synthesis, Structural and Optical Characterization of Zinc Doped Cadmium Sulphide Nanoparticles - Chauhan, Ruby; Kumar, Ashavani; Pal Chaudhary, Ram (Asian Journal of Chemistry, 2012)
Nanocrystals of undoped and zinc doped cadmium sulphide (Cd1-xZnx S, where x = 0.00 to 0.10) were synthesized by chemical precipitation method. Structural characterization of as synthesized semiconductor nanoparticles was performed by X-ray diffraction pattern while optical characterization were done by UV-Visible absorption spectroscopy. XRD pattern showed that the synthesized Zn doped CdS nanoparticles have wurtzite hexagonal structure with 3-39 nm average crystallite size. Optical absorption measurements indicated red shift in the absorption band edge upon Zn doping. Direct allowed band gap of undoped and Zn-doped CdS nanoparticles measured by UV-Visible spectrophotometer were 2.4 to 2.2 eV at 500 ºC.